Suppression of Th1 differentiation by tryptophan supplementation in vivo - Lanz, Tobias; Opitz, Christiane; Wick, Wolfgang; Platten, Michael (Amino acids, 2017)
Metabolism of the essential amino acid tryptophan (trp) is a key endogenous immunosuppressive pathway restricting inflammatory responses. Tryptophan metabolites promote regulatory T cell (Treg) differentiation and suppress proinflammatory T helper cell (Th)1 and Th17 phenotypes. It has been shown that treatment with natural and synthetic tryptophan metabolites can suppress autoimmune neuroinflammation in preclinical animal models. Here, we tested if oral intake of tryptophan would increase immunosuppressive tryptophan metabolites and ameliorate autoimmune neuroinflammation as a safe approach to treat autoimmune disorders like multiple sclerosis (MS). Without oral supplementation, systemic kynurenine levels decrease during the initiation phase of experimental autoimmune encephalomyelitis (EAE), a mouse model of MS, indicating systemic activation of tryptophan metabolism. Daily oral gavage of up to 10 mg/mouse/day was safe and increased serum kynurenine levels by more than 20-fold for more than 3 h after the gavage. While this treatment resulted in suppression of myelin-specific Th1 responses, there was no relevant impact on clinical disease activity. These data show that oral trp supplementation at subtoxic concentrations suppresses antigen-specific Th1 responses, but suggest that the increase in trp metabolites is not sustained enough to impact neuroinflammation.